The Impact of Night Markets Causing Congestion Case Study: At Gandu Village Square, Dawuan Subdistrict - Surya Natawibawa Kurnia; Mohammad Taufik; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
Traffic congestion is a major problem around the world. On a global level, the increase in the number of motorized vehicles has become a problem that causes congestion on roads. While there have been many studies on traffic congestion, there is little research on the specific impact of night markets on traffic congestion. This research aims to address the congestion problem by conducting a comprehensive literature review on the relationship between night markets and traffic congestion. In addition, this research also analyzed various related case studies to gain a deeper understanding of this issue. This research uses qualitative methods. Qualitative research understands social and natural phenomena by exploring the meaning and experiences of research subjects. Qualitative research emphasizes on understanding individual perspectives, contexts, and processes rather than quantitative research which focuses more on numbers and numerical data. The results show that a significant increase in the volume of motorized vehicles during peak hours is the main factor causing congestion in the Alun Alun Gandu area. Lack of road capacity, especially at four-way intersections and narrow roads, exacerbates congestion in the area. Unruly road user behavior, such as indiscriminate parking and traffic sign violations, also exacerbate congestion. Unexpected events such as traffic accidents or demonstrations can trigger widespread congestion and impact community mobility. This study found that the large number of private vehicles, lack of parking lots, and lack of public awareness of the importance of traffic order caused congestion around the Gandu night market on Tuesdays at 17.00-20.30 WIB. To overcome this, it is recommended to provide additional parking lots in vacant lots around the night market location and conduct socialization to visitors regarding good parking procedures. The conclusion obtained from the results of the vehicle speed test, at 17:35-18:25 WIB the lowest average vehicle speed reached 16.02 km / h, the speed of the vehicle appears to have decreased due to the increase in vehicle volume.